The repeated bout effect influences lower-extremity biomechanics during a 30-min downhill run - Khassetarash, A.; Baggaley, M.; Vernillo, G.; Millet, G. Y.; Edwards, W. B. (European Journal of Sport Science, 2023)
The repeated bout effect in eccentric-biased exercises is a well-known phenomenon, wherein a second bout of exercise results in attenuated strength loss and soreness compared to the first bout. We sought to determine if the repeated bout effect influences changes in lower-extremity biomechanics over the course of a 30-min downhill run. Eleven male participants completed two bouts of 30-min downhill running (DR1 and DR2) at 2.8 m/s and -11.3° on an instrumented treadmill. Three-dimensional kinematics and ground reaction forces were recorded and used to quantify changes in spatiotemporal parameters, external work, leg stiffness, and lower extremity joint-quasi-stiffness throughout the 30-min run. Maximum voluntary isometric contraction (MVIC) and perceived quadriceps pain were assessed before-after, and throughout the run, respectively. DR2 resulted in attenuated loss of MVIC (P = 0.004), and perceived quadriceps pain (P < 0.001) compared to DR1. In general, participants ran with an increased duty factor towards the end of each running bout; however, increases in duty factor during DR2 (+5.4%) were less than during DR1 (+8.8%, P < 0.035). Significant reductions in leg stiffness (-11.7%, P = 0.002) and joint quasi-stiffness (up to -25.4%, all P < 0.001) were observed during DR1 but not during DR2. Furthermore, DR2 was associated with less energy absorption and energy generation than DR1 (P < 0.004). To summarize, the repeated bout effect significantly influenced lower-extremity biomechanics over the course of a downhill run. Although the mechanism(s) underlying these observations remain(s) speculative, strength loss and/or perceived muscle pain are likely to play a key role.